KAJIAN PERILAKU INFORMASI MAHASISWA FAKULTAS ILMU BUDAYA UNIVERSITAS DIPONEGORO - Prasetyawan, Yanuar; Krismayanti, Ika (BACA: Jurnal Dokumentasi dan Informasi, 2025)
The aim of this study is to explore the student information behaviors of the Faculty of Humanities, UNDIP. Research uses quantitative methods to describe student behavior in information search. The study found that Google is the most popular site for the students when they are looking for information. However, they still use the primary resources such as academic journals as their main references. The study also found that the students have less used the subscribed academic databases. The identification of students’ information behavior is important as it will be used for the enhancement of UNDIP library services. The results of this study can also be used as a library reference for UNDIP in designing user education that will support the improvement of student information search skills.